2020
DOI: 10.5603/arm.2020.0071
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Right Ventricular Dysfunction in Patients with Idiopathic Pulmonary Hypertension versus Secondary Pulmonary Hypertension

Abstract: Introduction: Right ventricular (RV) function in the setting of pulmonary hypertension based on different etiologies has not been well studied. In this study, we evaluated the RV function in patients with idiopathic pulmonary hypertension (IPH) versus secondary pulmonary hypertension (SPH) due to congestive heart failure. Material and method: Forty-five patients with pulmonary hypertension and New York Heart Association (NYHA) functional class II or III were enrolled. Of these, 22 were diagnosed with IPH and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is easy to understand the divergent responses of RV to PH subtypes with different pathogenesis and pathophysiology. For example, Emami and colleagues found that patients with IPAH had better RV function compared to those with PH secondary to chronic heart failure (PH-HF) ( Emami et al, 2020 ). This study showed that patients with IPAH had higher peak systolic velocity of tricuspid annulus, higher dp/dt, and better RV free wall stiffness, but other RV parameters such as TAPSE and FAC are only slightly increased without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is easy to understand the divergent responses of RV to PH subtypes with different pathogenesis and pathophysiology. For example, Emami and colleagues found that patients with IPAH had better RV function compared to those with PH secondary to chronic heart failure (PH-HF) ( Emami et al, 2020 ). This study showed that patients with IPAH had higher peak systolic velocity of tricuspid annulus, higher dp/dt, and better RV free wall stiffness, but other RV parameters such as TAPSE and FAC are only slightly increased without reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%